2014
DOI: 10.1111/febs.12673
|View full text |Cite
|
Sign up to set email alerts
|

AML1–ETO triggers epigenetic activation of early growth response gene l, inducing apoptosis in t(8;21) acute myeloid leukemia

Abstract: The t(8;21)(q22;q22) translocation is the most common chromosomal translocation in acute myeloid leukemia (AML), and it gives rise to acute myeloid gene 1 (AML1)-myeloid transforming gene 8 (ETO)-positive AML, which has a relatively favorable prognosis. However, the molecular mechanism related to a favorable prognosis in AML1-ETO-positive AML is still not fully understood. Our results show that the AML1-ETO fusion protein triggered activation of early growth response gene l (EGR1) by binding at AML1-binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…To determine the role of RUNX1‐RUNX1T1 in the regulation of miR‐9–1‐5p expression, RUNX1‐RUNX1T1 was knocked out in SKNO‐1 cells (SKNO‐1‐siAE) using a lentiviral vector, and HA‐tagged RUNX1‐RUNX1T1 cDNA was electroporated into U937 cells to produce the U937‐AE‐HA clone in a zinc‐inducible manner . Knockdown and overexpression of RUNX1‐RUNX1T1 by western blot in SKNO‐1‐siAE and U937‐AE‐HA were validated, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the role of RUNX1‐RUNX1T1 in the regulation of miR‐9–1‐5p expression, RUNX1‐RUNX1T1 was knocked out in SKNO‐1 cells (SKNO‐1‐siAE) using a lentiviral vector, and HA‐tagged RUNX1‐RUNX1T1 cDNA was electroporated into U937 cells to produce the U937‐AE‐HA clone in a zinc‐inducible manner . Knockdown and overexpression of RUNX1‐RUNX1T1 by western blot in SKNO‐1‐siAE and U937‐AE‐HA were validated, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism(s) by which HDAC inhibitors induce EGR1 expression and activity was not investigated in this study. Previous work has shown that HDAC inhibitors can reactivate EGR1 in various cell types, leading to decreased cell proliferation and increased cell apoptosis [ 25 , 46 , 47 , 48 ]. Other mechanisms controlling EGR1 include various signaling pathways such as the EGF (Epidermal Growth Factor)/ELK1 (Ets domain containing protein) pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Contrary to the activating growth function, overexpression of Egr1 inhibited the cell proliferation and promoted apoptosis, and knocking out Egr1 promoted cell proliferation. 6 All of these indicate that the effects of Egr1 are complicated and may depend on the type of disease.…”
Section: Introductionmentioning
confidence: 99%